KONSEP IMPLEMENTASI PENDIDIKAN KARAKTER OLEH GURU PENDIDIKAN AGAMA KRISTEN BERDASARKAN BUAH ROH DALAM GALATIA 5:22-23 - sugiharto, eko; Mahendra, Yudha (Jurnal Teologi Biblika, 2026)
Abstract Character education is a learning process aimed at shaping and transforming students’ personalities to reflect the character of Christ based on the Word of God. The primary foundation of this study refers to Galatians 5:22–23 concerning the fruit of the Spirit, which encompasses three dimensions of character: relationship with God (love, joy, peace), relationship with others (patience, kindness, goodness), and relationship with oneself (faithfulness, gentleness, self-control). These three dimensions serve as a theological framework for developing a holistic and integrative character education.Character transformation is understood as a positive and effective process, meaning a change that aligns with educational goals and can be sustained and applied in daily life. Although character transformation is not easy—especially for individuals with certain tendencies such as being introverted or passive—it remains possible through changes in behavior patterns, habits, and self-beliefs. These behaviors include both reflective and non-reflective aspects and involve cognitive, affective, and motor dimensions within the individual.The findings of this study indicate that character education based on the fruit of the Spirit can be concretely operationalized in the learning process. Its implementation is carried out through Project-Based Learning (PBL), Classroom Action Research (CAR), and integrated counseling services. Through these strategies, character values are not only taught conceptually but also practiced in students’ real-life contexts.The study reveals a significant improvement in students’ positive behaviors, such as responsibility, discipline, and empathy. Therefore, this research contributes meaningfully to the development of a theologically grounded character education model that is not only conceptual but also practical and contextual in the educational setting. This model is expected to serve as a reference for forming a generation with a holistic Christian character. Keywords: Education, Character, Fruit of the Spirit